PEMBERITAAN MEDIA PENYIARAN TERKAIT PERISTIWA BENCANA GEMPA BUMI BERPOTENSI TSUNAMI (Analisis Wacana Kritis Naskah Siaran Radio Sindo Trijaya FM pada 11 April 2012) - DYAH RACHMAWATI (Communication, 2015)
This study aims to criticize the function of radio is not only as a medium of information, but also as a part of early warning chain of earthquake and tsunami.The lack of knowledge possessed by broadcasters in Indonesia, especially radio, seems as reason why media has not been optimal in the dissemination of the earthquake information and tsunami early warning BMKG. Based on the text analysis of Sindo Trijaya FM radio broadcasts, this study indicate those information broadcast against catastrophic events 11 April 2012 have mention several tsunami early warning messages which sent by the BMKG, but producers and broadcasters still seemed not to understand the meaning of warning messages. Cognition Journalists in Producing News Earthquake and Tsunami in Sindo Trijaya FM Radio in this study had started, but not supported by a written policy specifically regarding reporting procedures earthquake and tsunami disaster. Another facts is Disaster Issues in this radio is not a priority.